Formulating other minds in social interaction: accountability and courses of action - Zinken, Jörg; Kaiser, Julia (Language in society, 2022)
We examine moments in social interaction in which a person formulates what another thinks or believes. Such formulations of belief constitute a practice with specifiable contexts and consequences. Belief formulations treat aspects of the other person's prior conduct as accountable on the basis that it provided a new angle on a topic, or otherwise made a surprising contribution within an ongoing course of actions. The practice of belief formulations subjectivizes the content that the other articulated and thereby topicalizes it, mobilizing commitment to that position, an account, or further elaboration. We describe how the practice can be put to work in different activity contexts: sometimes it is designed to undermine the other's position as a subjective ‘mere belief’, at other times it serves to mobilize further topic talk. Throughout, belief formulations show themselves to be a method by which we get to know ourselves and each other as mental agents. (Accountability, beliefs, courses of action, formulations, inference, subjectivity, topicalization)*